Equal Sharing Rules in Partnerships - Björn Bartling; Ferdinand von Siemens (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
Partnerships are the prevalent organizational form in many industries. Most partnerships share profits equally among the partners. Following Kandel and Lazear (1992) it is often argued that peer pressure mitigates the arising free-rider problem. This line of reasoning takes the equal sharing rule as exogenously given. The purpose of our paper is to show that with inequity averse partners - a behavioral assumption akin to peer pressure - the equal sharing rule arises endogenously as an optimal solution to the incentive problem in a partnership.
urn:nbn:de:bvb:19-epub-13335-0
Keywords: D20; D86; J54; 330; equal sharing rule; partnerships; incentives; peer pressure; inequity aversion